Training medical students in motivational interviewing using a blended learning approach: a proof-of-concept study - Erschens, Rebecca; Fahse, Bettina; Festl-Wietek, Teresa; Herrmann-Werner, Anne; Keifenheim, Katharina E.; Zipfel, Stephan; Fallgatter, Andreas J.; Velten-Schurian, Kerstin (Frontiers in Psychology, 2023)
Background: Difficulties in implementing behaviour change in patients with chronic diseases are common in clinical practice. Motivational interviewing (MI) helps clinicians to support patients in overcoming ambivalence while maintaining self-determination. The inclusion of MI in German medical training curricula is still rare. Furthermore, the effects of systematic teaching of MI, especially via blended learning, have hardly been investigated.Methods: Medical students participated in three curricular events related to MI, consisting of instructional videos and theoretical and practical components in a blended learning format. The aim of the study was to investigate the effect of teaching MI in students' medical education. A controlled, non-randomised study was conducted with an intervention group and a control group. Both groups completed questionnaires on their experience and knowledge related to MI, completed a knowledge test and rated their satisfaction with the course. MI was taught in the 6 th semester of medical coursework as part of a psychosomatic course, in the 8 th semester during a psychiatry course and in the 9 th semester during a weekly psychiatry clerkship.Results: Data from the intervention group (n = 35) and control group (n = 14) were analysed, with 65.7% of students participating in all three parts of the curriculum. Overall interest in learning MI was high, with M = 2.92 (SD = 1.00). The results indicate a greater increase in knowledge over time in the intervention group. The majority (62.86%) stated that the curriculum was relevant to their future career. Free-form text responses indicated a high level of satisfaction with practical relevance.This study demonstrates the usefulness of an MI curriculum for medical students.